Faktor-faktor Penyebaran Ilmu Tata Bahasa Arab (Nahwu) - H Nour, Salwaa; Muttaqin, Zainal (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
Nahwu (Arabic grammar) is a discipline aimed at understanding texts in the Arabic language. It was first codified by Imam Abu Aswad al-Du’aly under the instruction of Imam Ali bin Abi Talib during his tenure as caliph. The development of Nahwu was influenced by three main factors within the Arab-Islamic cultural context: religious, national, and political factors. The religious factor emphasizes the importance of Nahwu in reciting and comprehending the Qur'an. The national factor highlights the role of Arabic grammar in shaping Arab-Islamic national identity. The political factor illustrates how the social classification between Arabs and mawlas impacted the dissemination and development of Arabic grammar. Thus, Nahwu not only serves as a tool for understanding religious texts but also plays a significant role in shaping national identity and responding to socio-political dynamics in Arab-Islamic society.